Development of efficiency improvement method of photovoltaic converters by nanostructurization of silicon wafers - Suchikova, Yana (Technology audit and production reserves, 2016)
The object of this research is the process of preparing silicon wafers for further use as the main component of solar panels. One of the problems in this process is the degradation of silicon in service and high rates of reflection coefficient, which greatly affects the PVC performance. The layers of porous silicon were formed by electrochemical etching in a solution of hydrofluoric acid at room temperature. This method is the most common for making porous semiconductors, due to the simplicity and low cost The technological modes of obtaining porous silicon layer were determined. The porous silicon was formed by electrochemical etching in a solution of hydrofluoric acid. Nitrogen passivation was used for stabilization of the properties. It was found that the thickness of the porous layer correlates with the etching time. The porosity shows a nearly linear dependence on the current density. The obtained results allow to state that porous silicon is a promising material for creation of solar cells on its base.